HOW TO BE MORE COMPETENT IN INTERNATIONAL MARKET? INTERNATIONAL STRATEGIC MANAGEMENT; CASE STUDY OF FGB PTY LTD, AUSTRALIA - DILLA NOVERITA (Jurnal Bisnis dan Akuntansi, 2005)
Felton Grimwade & Bickford Pty Ltd (PGB) is a long established company operating in the pharmaceutical industry, which mainly produced eucalyptus oil and other products containing natural ingredients. Currently, FGB is the market leader in the industry in which the company has a competitive advantage as being the largest eucalyptus oil procedures in the Australia. As their domestic market is saturated, the company has expanded their market internationally by exporting their products overseas. However due to the company’s private funding, FGB was frequently restrained to adopt new innovative international strategies. Further more, as a long established company, the management style was somewhat conventional in which the level of taking risk is very low. As a result of poor management attitude towards changes, FGB had become too dependent on their foreign distributor to act on behalf of the company, lacking of innovative strategies, which thus led to market stagnancy. The case study in this article highlighted the critical impact of these issues on FGB’s export performance and their current position in their international market. This article also analyzes what strategy alternatives that able to solve those issues so that the company could improve its current position in international market